Musical meaning in the piano piece The Little Cloth Bird by Heitor Villa-Lobos: interpreting musical gestures in search of characteristic traits (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
this article aims to investigate the phenomenon that occurs in the last measure of the piano piece The Little Cloth Bird by Heitor Villa-Lobos. This piece is part of the cycle Baby’s Family No. 2 from 1926. In desagreement with the other harmonic structures of the piece, the work in question enables an analysis under the point of view of Set Theory followed by an interpretation lined up with a possible intent evidenced by the title of the work and corroborated by dynamic markings and agogic.
Keywords: Villa-Lobos; A Prole do Bebê No. 2; Teoria dos Conjuntos; Significado Musical